Katutubo memory of dances (Quezon City Philippine Center for Investigative Journalism, 2001)
The film gives voice to the hopes of the indigenous peoples that they will relive the memory of their dances with the soles of their feet firmly touching the sacred ground that has been the homeland of their ancestors since time immemorial.
VHS format.
Director, Antonio Jose Perez ; concept, Sheila Coronel ; scriptwriter/supervising producer, Luz Rimban ; Cinematographer, Boy Yñiguez ; sound, Ernie Enrique ; music, Jaime Fabregas.
Narrators, Gary Granada.
Keywords: Indigenous peoples -- Philippines; Tagbanua (Philippine people) -- Social conditions; Ilongot (Philippine peopl) -- Social conditions; Manobos (Philippine peopl) -- Social conditions